Comparison of Internal and External Distraction in Frontofacial Monobloc Advancement: A Three-Dimensional Quantification - Rickart, Alexander J; van de Lande, Lara S; O' Sullivan, Eimear; Bloch, Kevin; Arnaud, Eric; Schievano, Silvia; Jeelani, Noor Ul Owase; Paternoster, Giovanna; Khonsari, Roman; Dunaway, David J (Plastic and reconstructive surgery (1963), 2023)
Crouzon syndrome is characterized by complex craniosynostosis and midfacial hypoplasia. Where frontofacial monobloc advancement (FFMBA) is indicated, the method of distraction used to achieve advancement holds an element of equipoise. This two-center retrospective cohort study quantifies the movements produced by internal or external distraction methods used for FFMBA. Using shape analysis, this study evaluates whether the different distraction forces cause plastic deformity of the frontofacial segment, producing distinct morphologic outcomes. Patients with Crouzon syndrome who underwent FFMBA with internal distraction [Hôpital Necker-Enfants Malades (Paris, France)] or external distraction [Great Ormond Street Hospital for Children (London, United Kingdom)] were compared. Digital Imaging and Communications in Medicine files of preoperative and postoperative computed tomographic scans were converted to three-dimensional bone meshes and skeletal movements were assessed using nonrigid iterative closest point registration. Displacements were visualized using color maps and statistical analysis of the vectors was undertaken. Fifty-one patients met the strict inclusion criteria. Twenty-five underwent FFMBA with external distraction and 26 with internal distraction. External distraction provides a preferential midfacial advancement, whereas internal distractors produce a more positive movement at the lateral orbital rim. This confers good orbital protection but does not advance the central midface to the same extent. Vector analysis confirmed this to be statistically significant ( P < 0.01). Morphologic changes resulting from monobloc surgery differ depending on the distraction technique used. Although the relative merits of internal and external distraction still stand, it may be that external distraction is more suited to addressing the midfacial biconcavity seen in syndromic craniosynostosis. Therapeutic, III.